Alternative investments : instruments, performance, benchmarks, and strategies - Baker, H. Kent (Harold Kent), 1944-; Filbeck, Greg. (Hoboken, New Jersey : Wiley, 2013)
A comprehensive guide to alternative investments that reveals today's latest research and strategies Historically low interest rates and bear markets in world stock markets have generated intense interest in alternative investments. With returns in traditional investment vehicles relatively low, many professional investors view alternative investments as a means of meeting their return objectives. Alternative Investments: Instruments, Performance, Benchmarks, and Strategies, can put you in a better position to achieve this difficult goal. Part of the Robert W. Kolb Series in.
Acknowledgments -- Introduction -- Alternative investments : an overview / H. Kent Baker, Greg Filbeck -- The role of alternative investments in strategic asset allocation / Douglas Cumming, Lars Helge Haá, Denis Schweizer -- Trends in alternative investments / Erik Benrud -- Alternative investments and due diligence / Gekhan Afyonolu -- Answers to discussion questions -- Index.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Investments; Asset allocation; Investment analysis; BUSINESS & ECONOMICS -- Investments & Securities -- General; Asset allocation; Investment analysis; Investments; Asset allocation; Electronic books; Electronic books